Accounting Profession and Evolution of Standard Setting in Iran - Jamal Roudaki (Journal of Accounting, Business and Management (JABM), 2008)
This article is an assessment of the Iranian accounting profession development and standards setting over the past 30 years. The focus of this article is standard setting development after 1979 Islamic Revolution of Iran. Iran Audit Organisation (IAO) established in 1987 by law to provide government financial services and set national accounting and auditing standards. In 1993 when the law of using accounting services of expert accountant as official tax accounts was approved, standard setting process sped up. As it was recommended by this law, the Ministry of Economic Affairs and Finance of Iran founded the Iranian Association of Certified Public Accountants (IACPA) as the first semi-private professional accounting society in 2001. Standard Board of IAO had introduced, 37 accounting and 33 auditing standards to the end of 2005. This board takes some steps to harmonize of National Accounting Standards (NASs) with International Accounting Standards (IASs).